Basic self-disturbance in subjects at clinical high risk for psychosis: Relationship with clinical and functional outcomes at one year follow-up. (June 2021) - Værnes, Tor Gunnar; Røssberg, Jan Ivar; Melle, Ingrid; Nelson, Barnaby; Romm, Kristin Lie; Møller, Paul
Highlights: Basic self-disturbance (BSD) predicted positive symptoms and dysfunction in CHR subjects. Baseline BSD also associated with future negative and disorganization symptoms. Higher levels of BSD were associated with non-remission of CHR states. Baseline negative symptoms and functioning also associated with remission. Levels of BSD in schizophrenia spectrum patients were in line with previous studies. Abstract: Basic self-disturbance (BSD) is assumed to drive symptom development in schizophrenia spectrum disorders and in clinical high-risk (CHR) for psychosis. We investigated the relationship between BSD at baseline, assessed with the Examination of Anomalous Self-Experience (EASE), and symptoms and functional outcome after one year in 32 patients, including 26 CHR and six with non-progressive attenuated psychotic symptoms. Correlations between baseline BSD levels and positive, negative and disorganization symptoms, and global functioning level at follow-up were significant. Hierarchical regression analyses revealed that higher levels of baseline BSD predicted more severe positive symptoms and lower global functioning at follow-up, after adjusting for baseline positive symptoms and functioning. Subjects who were not in symptomatic and functional remission after one year had higher levels of BSD and negative symptoms, and lower functioning level, at baseline. Baseline BSD in participants with schizophrenia spectrum diagnoses at follow-up (9 of 12 were schizotypal personality disorder) were at the levels seen in schizotypal disorders in previous studies, but not significantly different from the other participants. Early identification and assessment of BSD may constitute a useful prognostic tool and a signal for therapeutic targets in CHR conditions. Further CHR studies investigating these relationships with larger samples are recommended.